I lost my image, the image others know me by: findings from a hermeneutic phenomenological study of patients living with treatment-induced cutaneous toxicities - Charalambous, Andreas; Charalambous, Melanie (My University, 2016)
Cancer patients receiving targeted therapies often develop persistent cutaneous adverse effects, such as papulopustular eruption (rash), xerosis cutis (dry skin), pruritus (itch), and hair and nail changes. These can be dose-limiting or a cause for therapy discontinuation but also can be wearing on patients, negatively influencing their self-image and relationships with others. In a Ricoeurian hermeneutic phenomenological study, we aimed to explore the lived experiences of colorectal, pancreatic, and non-small cell lung cancer patients living with cutaneous toxicities following treatment with targeted agents. Narratives were used to elicit the experiences of 22 cancer patients. Data were analyzed in three steps informed by Ricoeur's interpretation theory: naïve understanding, structural analyses, and comprehensive understanding. Three themes were identified: "Ashamed of what I have become," "Surrender to cancer," and "Mourning for the loss of my body," with nine sub-themes revealing the multidimensional impact of the adverse effects on the patients' lives. The comprehensive understanding produced in analysis revealed a new contextualized interpretation of being in the world while living with cutaneous toxicities. Treatment-induced cutaneous toxicities distorted patients' daily living in ways that led to negative manifestations and effects on their self-image, social engagement, and intimate relationships. Although the dose-limiting and treatment-interrupting effects of these toxicities have been reported, this study sheds light on their existential impact, touching on physical, psychological, and social issues.
Keywords: Cancer; Cutaneous toxicities; Hermeneutic phenomenological; Lived experience; Self-image; Side effects; Skin integrity